Difusi Inovasi Pelayanan Publik Berbasis Digital Dalam Aplikasi SIPADU di Desa Dangin Puri Kangin, Kota Denpasara, Kota Denpasar - Dewi, Ni Kadek Tasya Pranawa Dewi; Kalpika Putri, Ni Putu Dinda (Department of Public Administration, Muhammadiyah University of Makassar, 2026)
Digital Dangin Puri Kangin Village has implemented the SIPADU application as digital innovation to improve public service delivery. Despite its potential, the adoption process faces several challenges, including limited utilization, insufficient socialization, and the need for further feature development. This study aims to analyze how the adoption of SIPADU contributes to effective and efficient public services. Using a descriptive qualitative approach, data were collected through interviews with village officials and service users. The result show that SIPADU meets key innovation characteristics, such as relative advantage, compatibility with community needs and ease of use. The diffusion process is supported by both interpersonal communication and digital media, enhancing public awareness. However, the adoption has not yet reached full implementation, as many residents still prefer direct, face-to-face services. Overall, the study highlights that digital innovation at the village level is influenced by technological readiness, institutional support, and existing social practices.